Autologous stem cell transplantation in the treatment of multiple myeloma single center experience - Marjanović Slobodan; Stamatović Dragana; Tukić Ljiljana; Tarabar Olivera; Elez Marija; Mađaru Lavinika; Balint Bela; Tatomirović Željka; Kuljić-Kapulica Nada; Anđelković Nebojša (Vojnosanitetski Pregled)
Background/Aim. In comparison to standard therapy autologous stem cell transplant (ASCT) with high doses melphalane has improved treatment of multiple myeloma (MM) patients. The aim of this study was to evaluate the results of treatment of MM patients in our center with ASCT conditioning with melphalane or combining busulphane, cyclophosphamide and melphalane. Methods. We performed 62 ASCT procedures in 47 patients from 1998 till 2008. Single ASCT were performed in 32 patients (68%), after 3-6 cycles of vincristine, adriamycin, dexamethasone (VAD) protocol and double in 9 patients (19%). Secondary ASCT was performed in 6 (13%) patients during progression of the disease after single ASCT. Mobilization of stem cells (SC) was either with a combination of etoposide and cyclophosphamide with granulocyte colony-stimulating factor (G-CSF) in 39 (83%) patients or cyclophosphamide plus G-CSF in 8 (17%) patients. All the patients received G-CSF five days after the ASCT and maintenance therapy afterwards in the patients with a complete remission (CR) or a partial remission (PR) was interferon alpha in 14 (30%) patients, thalidomide in 13 (28%) and others in 12 (26%) patients. Results. Median engraftment was on 12th day. In a 50-month follow-up period 64% patients were alive. The overall response rate (ORR), which was reached in 38 (80%) patients, was better in the group of patients treated in the early phase of MM. Totally 25 (53%) patients were without progression in a 25-month follow-up period. Twenty patients met criteria for CR + VGPR (very good partial remission), that was 5 patients more than in the period before ASCT. Fourteen (30%) patients died and median time till death was 17 months. Conclusion. The ASCT perfomed in early phase of MM after VAD induction had a significant influence on the treatment of MM patients. Reaching CR + VGPR before and after the ASCT is predictive factor for overall survival (OS) or prolongation of period till recidive appears, progression, therapy withdrowal or death.